Penanaman Karakter Religius dan Disiplin Melalui Program Literasi Qur’an pada Siswa Sekolah Menengah Atas Muhammadiyah 2 Gemolong Tahun Ajaran 2025/2026 - Azizah, Alfi Nur; Nashir, Muhammad Ja’far (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to describe the process of cultivating religious and disciplined character through the Qur’anic Literacy Program and to identify supporting and inhibiting factors in its implementation at Muhammadiyah 2 Gemolong Senior High School in the 2025/2026 academic year. This research employs a qualitative approach with data collected through observation, in-depth interviews, and documentation. The participants include the principal, vice principal for curriculum, tahfidz teachers, and students. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the Qur’anic Literacy Program, conducted through daily Qur’an reading (PBQ) and memorization activities, effectively fosters students’ religious awareness, discipline, and positive behavior. The success of the program is supported by strong school management commitment, active teacher involvement, parental support, students’ internal motivation, and adequate facilities. However, several challenges were identified, such as student lateness, boredom during memorization sessions, and schedule adjustments due to reduced instructional time. Overall, the program significantly contributes to shaping students’ religious and disciplined character, although continuous innovation and evaluation are needed to optimize its implementation.